Selective formation of glycosidic linkages of N-unsubstituted 4-hydroxyquinolin-2-(1H)-ones - Kimmel, Roman; Kafka, Stanislav; Kosmrlj, Janez (Carbohydrate research, 2010)
A comparative study for selective glucosylation of N-unsubstituted 4-hydroxyquinolin-2(1H)-ones into 4-(tetra-O-acetyl-beta-D-glucopyranosyloxy)quinolin-2(1H)-ones is reported. Four glycosyl donors including tetra-O-acetyl-alpha-D-glucopyranosyl bromide, beta-D-glucose pentaacetate, glucose tetraacetate and tetra-O-acetyl-alpha-D-glucopyranosyl trichloroacetimidate were tested, along with different promoters and reaction conditions. The best results were obtained with tetra-O-acetyl-alpha-D-glucopyranosyl bromide with Cs(2)CO(3) in CH(3)CN. In some cases the 4-O-glucosylation of the quinolinone ring was accompanied by 2-O-glucosylation yielding the corresponding 2,4-bis(tetra-O-acetyl-beta-D-glucopyranosyloxy)quinoline. Next, 4-(tetra-O-acetyl-beta-D-glucopyranosyloxy)quinolin-2(1H)-ones were deacetylated into 4-(beta-D-glucopyranosyloxy)quinolin-2(1H)-ones with Et(3)N in MeOH. In some instances the deacetylation was accompanied by the sugar-aglycone bond cleavage. Structure elucidation, complete assignment of proton and carbon resonances as well as assignment of anomeric configuration for all the products under investigation were performed by 1D and 2D NMR spectroscopy.
Keywords: Molecular Structure; hydroxychinoliny; molekulární struktura; magnetická rezonanční spektroskopie; Hydroxyquinolines; Magnetic Resonance Spectroscopy; Glycosylation; glykosylace